Economic Affectation of the Colombian State Due to Tax Evasion in the Customs Regime - Andres Adolfo Zapata Grisales; Sergio Antonio Restrepo Erazo; Orlando Carmelo Castellanos Polo (International Journal of Economics, Business Management and Accounting (IJEBMA), 2020)
The fundamental purpose of this investigation is to determine the different origins that taxpayers have in the different regions of Colombia for not appearing and paying the national customs tax, becoming tax fraud. When we examine the education of taxpayers in customs and the payments they make, we can determine through the Tax Administration that the level of evasion is lower every day. The approach that we want to make known is with an analysis in the Dian databases, in the database of the Inspection and Determination group of the sectional tax department of all the municipalities of Colombia. The population that was employed was determined by natural and legal persons, that carry out tax activities in the customs tax which is equivalent to 3,496 taxpayers. As a consequence, it is analyzed that, if there is a greater inspection with the taxpayers, important information and excellent follow-up in the presentation and remuneration of the tax, the level of evasion will be lower and lower. It is important that taxpayers have an understanding of the rules and laws of each department and municipality to determine that the non-presentation and payment of the Tax will give sanctions, interest for default and administrative acts